Слава – родинне свято у сербів - Раденкович, Л. (Народна творчість та етнологія, 2015)
Родинне свято в сербів, яке відбувається щороку у визначений день на честь одного зі святителів, називається слава, хресна слава, хресне ім’я тощо. Основною обрядодією цього свята є розрізання та розламування дріжджового хліба, який має назву славський колач. У західних сербських областях під час слави господар обирає поважного гостя, який керує обрядами (долибаша), він не сідає за стіл, а піклується, аби всіх гостей почастували їжею та напоями. У цих місцевостях узвичаєно, що всі чоловіки під час розрізання колача стоять з непокритою головою і разом співають славську пісню. У Східній Сербії кожний гість, який приходить на славу, спочатку цілує спеціальний хліб на столі, а потім вітається з господарем та всіма іншими. Тут спорадично засвідчена практика, коли господар перед розрізанням короваю, тримаючи запалену свічку, вклоняється та цілує землю. Слава початково була святом на честь міфічного божества, засновника роду, який уособлював усіх предків певного роду. Породични празник код Срба који се одржава сваке године у одређени дан у част негог од светитеља назива се слава, крсна слава, крсно име итд. Главни обред на слави јесте резање и ломљење квасног хлеба, који се назива славски колач. У западним српским крајевима, на слави домаћин бира угледног госта који руководи обредима (долибаша), а он не седа за сто, већ брине да сви гости буду послужени јелом и пићем. У овим крајевима приликом резања колача, сви мушкарци стојећи и гологлави, заједно певају уобичајену славску песму. У источној Србији, сваки гост који дође на славу, прво пољуби посебан хлеб на столу, па се онда поздравља са домаћином и укућанима. Овде је спорадично посведочена и пракса да се домаћин, пре резања колача, уз упаљену свећу, клања и љуби земљу. Слава је првобитно била празник посвећен митском претку, родоначелнику, који представља и укупност свих предака једног рода. The slava, krsna slava, or krsno ime is a family feast among the Serbs, which is celebrated every year on a given day, honoring a Christian saint who is the protector of a given family. The main ceremony at the slava is the cutting and breaking of the leavened bread – called slavski kolač, and the ritual pouring of the wine while saying a toast. In western Serbian regions, the head of a family chooses a reputable guest to administer the slava ceremonies (dolibaša), and he, in turn, does not sit down at the table but cares that all the guests are regaled with meals and drinks. In these Serbian parts, the rule is for men to stand bareheaded while cutting kalach and singing common slava songs together. In southern and eastern Serbia, each guest attending the slava first kisses the bread on the table and afterward salutes the host. There is also the sporadically recorded practice of a family head lighting a candle, bowing low, and kissing the ground before cutting the bread. The slava was originally a holiday dedicated to the mythical ancestor, the founder of a family, who together with other ancestors was considered the protector of all living descendents and their property. The Middle Over Dnipro Lands represent the integral characteristics of Ukrainian folklore tradition. On Right-Bank Ukraine, they bear resemblance with Eastern Podillia, while on the Left-Bank Lands – spread, without essential distinctions, to Slobozhanshchyna. The folklore of the Middle Over Dnipro Lands has its peculiarities. Thus, to the south of Chernihivshchyna along the Dnipro River, the traditional koliadky (Christmascarols), vesnianky (spring songs), and summer (Kupala, St. Peter’s fast, and harvest-related) songs slowly decrease in prevalence. The biblical themes grow dominant in Koliadky there.